On the traceability of gaseous reference materials. (30th May 2017) - Brown, Richard J C; Brewer, Paul J; Harris, Peter M; Davidson, Stuart; van der Veen, Adriaan M H; Ent, Hugo
Abstract: The complex and multi-parameter nature of chemical composition measurement means that establishing traceability is a challenging task. As a result incorrect interpretations about the origin of the metrological traceability of chemical measurement results can occur. This discussion paper examines why this is the case by scrutinising the peculiarities of the gas metrology area. It considers in particular: primary methods, dissemination of metrological traceability and the role of documentary standards and accreditation bodies in promulgating best practice. There is also a discussion of documentary standards relevant to the NMI and reference material producer community which need clarification, and the impact which key stakeholders in the quality infrastructure can bring to these issues.